DEVELOPMENT AND IN-VITRO DRUG RELEASE STUDIES OF SATRANIDAZOLE CAPSULES FOR COLON SPECIFIC DRUG DELIVERY - Rani P, Sobhita; Prasanna, Muthu; Kavya, Kadali (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of the present study is to formulate and evaluate carbopol based enteric capsules for site specific drug delivery of Satranidazole to colon which was used in the treatment of amoebiasis. Methodology: 10 different formulations of carbopol based Satranidazole capsules were prepared and coated with different ratios of HPMC and Eudragit S-100. The capsules were evaluated for various physic chemical parameters. The formulations were capable of delaying drug release in the time period of 3-5 h in the simulated physiologic environment of upper gastrointestinal tracts depending on coating ratios of HPMC and Eudragit S-100. Dissolution studies of all the formulations were performed and the cumulative percentage drug release for Satranidazole was calculated. Results: Dissolution studies demonstrate that, these polymeric coated formulations were gastro resistance for 2 h at 0.1 N Hcl and further for 3 h at pH 6.8; since they released only 7-9% of drug in physiological environment of stomach and small intestine. They showed better drug release in colonic region (pH 7.4) only. Bio-adhesive studies and Rheological studies reveal that carbopol is effective in pH 7.4 than 0.1 N Hcl and pH 6.8 buffers. Diffusion studies and Histopathological studies show that the drug can easily penetrate though the mucosal membrane. DSC and IR analysis shows no possibility of interaction between drug and polymers used in the study. Conclusion: Studies demonstrated that the developed system can be a promising device for targeting of Satranidazole to colonic region. Key words: Colon specific drug delivery, Histopathology, pH sensitive polymer, Satranidazole.